Self-repairing crystal anti-seepage high-durability cement-based material, cement-based ground structure and paving method of cement-based ground structure
By adding specific chelating agents and crystallization precipitants to the cement-based material, the problem of microcracks is realized in the process of use of the material, which improves the strength, durability and anti-seepage of the material, and simplifies the construction process.
Patent Information
- Application Number
- CN202411872445.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-18
AI Technical Summary
Cement-based materials are prone to microcracks during use, resulting in a decrease in the strength of the material and are easily penetrated by water molecules and chloride ions, causing leakage and strength loss, affecting durability.
A self-healing crystal anti-seepage high-durability cement-based material was developed. By adding diethylenetriamine pentaacetic acid as a chelating agent and sodium silicate, sodium carbonate, potassium fluoride, etc. to the material as a crystal precipitation agent, the reaction of calcium ion chelates and crystal precipitation agent is used to form crystal precipitation filling cracks, achieving self-healing.
This material can automatically repair microcracks during use, significantly improving strength, durability and anti-seepage properties, simplifying the construction process, and avoiding the application process.
Smart Images

Figure BDA0005196082550000051 
Figure BDA0005196082550000052 
Figure BDA0005196082550000061
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of building materials, and specifically relates to self-repairing crystal anti-seepage high-durability cement-based materials, cement-based ground structures and paving methods thereof. Background Art
[0002] At present, the mainstream material in the construction field is still cement-based material. A large number of house buildings and municipal floors use cement-based materials. However, cement-based materials will inevitably produce microcracks, resulting in reduced material strength. The presence of cracks also gives water molecules and chloride ions the opportunity to penetrate, causing leakage, which further causes material strength loss and affects durability.
[0003] Currently, there are penetrating crystalline waterproof materials on the market that can be used to repair microcracks generated by cement-based materials. For example, the Chinese patent with announcement number CN110105025A discloses a cement-based penetrating crystalline waterproof material. Its use method is: apply the waterproof material to the surface of cement concrete, and the active ingredients in the waterproof material migrate to the cracks and pores of the cement concrete in a water environment to undergo a crystallization reaction, generating water-insoluble crystals to fill the cracks and pores, thereby achieving the purpose of repairing microcracks. However, when using this type of penetrating crystalline waterproof material for repair, a coating process needs to be implemented, so the inventor of this application thought of developing a self-repairing cement-based material that can eliminate the waterproof material coating process, thereby simplifying the construction process. Summary of the invention
[0004] The purpose of this application is to provide a self-repairing crystal anti-seepage and highly durable cement-based material, a cement-based pavement structure and a paving method thereof. The cement-based material of this application can self-repair the micro-cracks generated during use, and while simplifying the construction process, it also has excellent anti-seepage and durability.
[0005] On the one hand, the present application provides a self-repairing crystal anti-seepage high-durability cement-based material, comprising the following components in parts by weight:
[0006] 40-60 parts of Portland cement, 35-50 parts of wear-resistant aggregate, 0.02-0.05 parts of water reducer, 0.2-0.5 parts of retarder, 1-2 parts of redispersible latex powder, 1-2 parts of silica fume, 1-3 parts of expansion agent, 1-6 parts of chelating agent, 1-6 parts of crystal precipitating agent; all the above components total 100 parts; wherein, the chelating agent is diethylenetriaminepentaacetic acid, and the weight ratio of the chelating agent to the crystal precipitating agent is (0.5-2):1.
[0007] In some embodiments, the chelating agent is 2 to 5 parts, and the crystalline precipitating agent is 2 to 5 parts, wherein the weight ratio of the chelating agent to the crystalline precipitating agent is (0.65 to 1.2):1.
[0008] In some embodiments, the chelating agent is 3 to 5 parts and the crystalline precipitating agent is 2.5 to 5 parts, wherein the weight ratio of the chelating agent to the crystalline precipitating agent is (0.75 to 1.2):1.
[0009] In some embodiments, the wear-resistant aggregate is selected from one or more of corundum, high-silicon quartz sand, and ceramic particles.
[0010] In some embodiments, the water reducing agent is a polycarboxylate water reducing agent.
[0011] In some embodiments, the retarder is sodium gluconate.
[0012] In some embodiments, the expansion agent is selected from calcium sulfoaluminate and / or calcium oxide.
[0013] In some embodiments, the crystalline precipitant is selected from one or more of sodium silicate, sodium carbonate and potassium fluoride.
[0014] On the other hand, the present application provides a cement-based ground structure, whose layered structure is: including a concrete base layer, an interface layer and a ground layer in sequence; wherein the raw material of the ground layer is the above-mentioned self-repairing crystal anti-seepage and high-durability cement-based material.
[0015] On the other hand, the present application provides a paving method for the above-mentioned cement-based ground structure, comprising:
[0016] Applying interface agent on the concrete base to form an interface layer;
[0017] The cement-based material is added with water to form a slurry, which is spread on the interface layer and cured to form a ground layer; wherein 12 to 16 parts by weight of water are added for every 100 parts by weight of the cement-based material.
[0018] Compared with the prior art, this application has the following advantages and beneficial effects:
[0019] 1. The cement-based material of the present application has self-repairing properties: when microcracks and water seepage occur in the cement-based material during maintenance and / or use, diethylenetriaminepentaacetic acid chelates with calcium ions in the cement-based material, and the calcium ion chelate flows through the cracks with the water flow. In this process, the crystal precipitant reacts with the calcium ion chelate to form a large amount of crystal precipitation, which fully fills the cracks and realizes self-repair of the cracks. The excellent self-repairing property can significantly improve the strength, durability and impermeability of the cement-based material.
[0020] 2. The strength of the cement-based material of the present application is significantly improved: when the cracks are self-repaired, the physical strength is enhanced; at the same time, the calcium ions chelated with the chelating agent mainly come from the hydration product of cement, calcium hydroxide, and the expansion agent. The consumption of calcium ions can reduce the calcium hydroxide content in the cement-based material, thereby enhancing the physical strength.
[0021] 3. This application selects diethylenetriaminepentaacetic acid as a chelating agent. Compared with other common chelating agents and complexing agents, the combination of diethylenetriaminepentaacetic acid chelating agent and crystallization precipitant can more significantly improve the physical strength, durability and impermeability of cement-based materials.
[0022] 4. In some embodiments of the present application, sodium gluconate is selected as a retarder, which, while playing the role of a retarder, can also promote the chelation of the chelating agent with calcium ions and promote the self-repair of cement-based materials.
[0023] 5. The present application uses flexural strength and compressive strength to characterize the physical strength of the sample, uses the 28d strength loss rate after 50 freeze-thaw cycles to characterize the durability of the sample, and uses the 28d impermeability pressure to characterize the impermeability of the sample. Compared with the use of other chelating agents (see Comparative Example 4), the flexural strength of the present application can be increased by about 11%, the compressive strength can be increased by 17%, the strength loss rate can be reduced by about 21%, and the impermeability pressure can be increased by about 19% (see Example 5). DETAILED DESCRIPTION
[0024] In order to make the purpose, technical solutions and beneficial effects of the present application more clear, the present application is further described in detail below in conjunction with embodiments.
[0025] The self-repairing crystal anti-seepage high-durability cement-based material provided by the present application comprises the following components in parts by weight: 40-60 parts of silicate cement, 35-50 parts of wear-resistant aggregate, 0.02-0.05 parts of water reducer, 0.2-0.5 parts of retarder, 1-2 parts of redispersible latex powder, 1-2 parts of silica fume, 1-3 parts of expansion agent, 1-6 parts of chelating agent, and 1-6 parts of crystallization precipitant; wherein the chelating agent is diethylenetriamine pentaacetic acid, and the weight ratio of the chelating agent to the crystallization precipitant is (0.5-2):1. All the above components total 100 parts by weight.
[0026] When microcracks are generated in cement-based materials and water seeps in, diethylenetriamine pentaacetic acid chelates with calcium ions in cement-based materials to form a ring-shaped calcium ion chelate, which flows through the cracks with water. In this process, a crystal precipitant reacts with the calcium ion chelate to form a large amount of crystal precipitation, which fully fills the cracks and closes them, thereby enhancing the strength, impermeability and durability of cement-based materials. In this application, calcium ions mainly come from calcium hydroxide, a cement hydration product, and an expansion agent. The consumption of calcium ions can reduce the calcium hydroxide content in cement-based materials, which helps to further enhance the physical strength of the material.
[0027] In some embodiments, silicate cement is selected with a strength grade of 52.5; the wear-resistant aggregate can be selected from one or more of corundum, high-silicon quartz sand, and ceramic particles, and the particle size is preferably 10-20 mesh; the water reducer can be selected from polycarboxylic acid water reducer; the retarder can be selected from sodium gluconate; the expansion agent can be selected from calcium sulfoaluminate and / or calcium oxide; the crystallization precipitant can be selected from one or more of sodium silicate, sodium carbonate and potassium fluoride.
[0028] In some embodiments, the silicate cement is 45-50 parts, 45-52 parts or 50-52 parts. In some embodiments, the wear-resistant aggregate is 35.55-47.78 parts, 35.55-47.28 parts, 35.55-46.28 parts or 35.55-37.77. In some embodiments, the expansion agent is 1-2 parts.
[0029] Water reducer is a common admixture for cement-based materials, mainly used to improve the workability of cement-based materials and reduce the unit water consumption. In this application, water reducer can be added in conventional amounts. In some embodiments, the water reducer is 0.02 to 0.03 parts or 0.03 to 0.05 parts.
[0030] Retarder is used to slow down the hardening time, which can reduce the hydration heat generated during the cement hydration process and reduce the generation of cracks. Retarder is also a common admixture for cement-based materials, and sodium gluconate can be selected. In this application, the retarder can be added in a conventional amount. In some embodiments, the retarder is 0.2 to 0.4 parts. When sodium gluconate is selected as the retarder, its dosage is preferably 0.3 to 0.5 parts. Excess sodium gluconate can promote the chelation of the chelating agent with calcium ions, thereby promoting crack closure.
[0031] In the present application, the weight proportion of the chelating agent and the crystallization precipitating agent should not be too small. When it is too small, the performance improvement of the cement-based material is not obvious; the weight proportion of the chelating agent and the crystallization precipitating agent should not be too large. When it is too large, although the strength loss rate after freeze-thaw cycles can be significantly reduced and still has excellent anti-seepage pressure, the strength is lost.
[0032] In some embodiments, the chelating agent is 2 to 5 parts, the crystal precipitating agent is 2 to 5 parts, and the weight ratio of the chelating agent to the crystal precipitating agent is (0.5 to 1.5): 1 or (0.55 to 1.5): 1 or (0.65 to 1.2): 1. In some embodiments, the chelating agent is 3 to 5 parts, the crystal precipitating agent is 2.5 to 5 parts, and the weight ratio of the chelating agent to the crystal precipitating agent is (0.65 to 1.2): 1 or (0.75 to 1.2): 1.
[0033] In some preferred embodiments, the self-repairing crystal anti-seepage high-durability cement-based material provided by the present application includes the following components in parts by weight: 45-52 parts of silicate cement, 35-47 parts of wear-resistant aggregate, 0.02-0.05 parts of water reducer, 0.2-0.4 parts of retarder, 1-2 parts of redispersible latex powder, 1-2 parts of silica fume, 1-2 parts of expansion agent, 2-5 parts of chelating agent, and 2-5 parts of crystallization precipitant; wherein the chelating agent is diethylenetriamine pentaacetic acid, and the weight ratio of the chelating agent to the crystallization precipitant is (0.65-1.2): 1. All the above components total 100 parts by weight.
[0034] In some preferred embodiments, the self-repairing crystalline anti-seepage and high-durability cement-based material provided by the present application includes the following components in parts by weight: 50-52 parts of silicate cement, 35-38 parts of wear-resistant aggregate, 0.03-0.05 parts of water reducer, 0.2-0.4 parts of retarder, 1.5-2 parts of redispersible latex powder, 1-2 parts of silica fume, 1-2 parts of expansion agent, 3-5 parts of chelating agent, and 2.5-5 parts of crystallization precipitant; wherein, the chelating agent is diethylenetriaminepentaacetic acid, and the weight ratio of the chelating agent to the crystallization precipitant is (0.75-1.2):1; all the above components total 100 parts by weight.
[0035] The cement-based material provided in the present application has a layered structure that includes a concrete base layer, an interface layer and a ground layer in sequence; the raw material of the ground layer is the above-mentioned cement-based material. The interface layer is used to enhance the adhesion of the concrete base layer, so that the concrete base layer and the ground layer can be more tightly bonded, and the interface layer can be optionally an acrylic emulsion interface agent.
[0036] The paving method of the cement-based ground structure provided in the present application comprises:
[0037] (1) Applying an interface agent on the concrete base to form an interface layer; the interface agent may be an acrylic emulsion interface agent;
[0038] (2) adding water to the cement-based material to form a slurry, spreading the slurry on the interface layer, and curing to form a ground layer;
[0039] In some embodiments, 12 to 16 parts by weight of water are added for every 100 parts by weight of cement-based material; the paving thickness of the slurry is 5 to 10 mm; and the curing is natural curing for no less than 24 hours.
[0040] Several embodiments and comparative examples are provided below. The raw materials used in the embodiments and comparative examples are as follows:
[0041] Cement: Huaxin PI52.5 silicate cement; wear-resistant aggregate: commercially available 10-20 mesh high-silica quartz sand, of which the silicon dioxide content is ≥95%; water reducer: Longhu P20 powder polycarboxylic acid water reducer; retarder: commercially available industrial-grade sodium gluconate powder; redispersible latex powder: Wacker 328 rubber powder; silica fume: commercially available, particle size 825 mesh; expansion agent: commercially available calcium sulfoaluminate and commercially available calcium oxide are compounded in a weight ratio of 1:1; chelating agent: diethylenetriaminepentaacetic acid from Hengjingrui Chemical, CAS: 67-43-6; crystallization precipitant: sodium silicate powder from Pengcai Chemical; ethylenediaminetetraacetic acid: white crystalline powder, commercially available industrial grade; sodium methyl silicate: white powder, Jinan Yueruida Chemical.
[0042] The components and the amounts of the components in the examples and comparative examples of the present application are listed in Table 1 and Table 2, respectively.
[0043] Table 1 Components and dosage of each component in the embodiment
[0044]
[0045] Table 2 Components and dosage of each component in the comparative example
[0046]
[0047]
[0048] The above-mentioned examples and comparative examples are prepared by the following method: mix the raw materials according to weight, then add water and stir to obtain a slurry, wherein the weight ratio of the water to raw material mixture is 15:100. The slurry is made into a sample, and the various performance indicators of the sample are tested. The 28d flexural strength and 28d compressive strength of the sample are tested with reference to the standard GB / T 50081-2019; the sample is subjected to 50 freeze-thaw cycles by the slow freezing method, and then the 28d compressive strength loss rate of the sample is tested with reference to the standard GB / T 50082-2009; the 28d impermeability pressure of the sample is tested with reference to the standard GB / T 50082-2009. The performance index test data are listed in Table 3 and Table 4 respectively. In this application, the 28d compressive strength loss rate is used to characterize the durability of the sample, and the 28d impermeability pressure is used to characterize the impermeability of the sample.
[0049] Table 3 Performance test data of the product of the embodiment
[0050]
[0051] Table 4 Performance test data of comparative products
[0052]
[0053] From Tables 1 to 4 above, it can be seen that adding a chelating agent or complexing agent in combination with a crystallization precipitant can improve the strength, durability and impermeability of the sample. When a chelating agent or complexing agent is used alone, although calcium ions can be aggregated through chelation or complexing effects, it is difficult to form water-insoluble crystalline precipitates to fill cracks, and the performance of the sample is not improved. When a crystallization precipitant is used alone, the crystallization precipitant can react with unaggregated calcium ions to form water-insoluble crystalline precipitates. Since a large amount of crystalline precipitates cannot be formed, the crack filling is limited, and the performance of the sample is also difficult to significantly improve.
[0054] In comparative example 4, the chelating agent is ethylenediaminetetraacetic acid, in comparative example 5, the complexing agent is sodium methyl silicate, and in the present application, the chelating agent is diethylenetriaminepentaacetic acid. By comparison, it can be seen that relative to comparative examples 4 to 5, the strength, durability and impermeability of the sample of the present application can be further improved, that is, the combination of diethylenetriaminepentaacetic acid chelating agent and crystallization precipitant can significantly improve the strength, durability and impermeability of cement-based materials.
[0055] The applicant believes that the mechanism by which the diethylenetriamine pentaacetic acid chelating agent can produce the above-mentioned technical effects is:
[0056] Compared with ethylenediaminetetraacetic acid chelating agent, the structure of diethylenetriaminepentaacetic acid has one more amino group and one more carboxyl group, which can combine with more calcium ions to form chelates, improve the density and transportation efficiency of calcium ions, and the crystal precipitant and the chelate with high calcium ion density can form a large amount of crystal precipitation to fully fill the cracks. Compared with sodium methyl silicate complex, diethylenetriaminepentaacetic acid can combine with calcium ions to form a more stable ring structure chelate, improve the transportation efficiency of calcium ions, and help to fully fill the cracks.
[0057] Note that the above are only preferred embodiments of the present application and the technical principles used. Those skilled in the art will understand that the present application is not limited to the specific embodiments described herein, and that various obvious changes, readjustments and substitutions can be made by those skilled in the art without departing from the protection scope of the present application. Therefore, although the present application is described in more detail through the above embodiments, the present application is not limited to the above embodiments, and may also include more other equivalent embodiments without departing from the concept of the present application, all of which belong to the protection scope of the present application.
Claims
1. A self-repairing crystal anti-seepage high-durability cement-based material, characterized by comprising: The following components in parts by weight: 40-60 parts of Portland cement, 35-50 parts of wear-resistant aggregate, 0.02-0.05 parts of water reducer, 0.2-0.5 parts of retarder, 1-2 parts of redispersible latex powder, 1-2 parts of silica fume, 1-3 parts of expansion agent, 1-6 parts of chelating agent, 1-6 parts of crystal precipitating agent; all the above components total 100 parts; wherein, the chelating agent is diethylenetriaminepentaacetic acid, and the weight ratio of the chelating agent to the crystal precipitating agent is (0.5-2):
1.
2. The self-repairing crystal anti-seepage high-durability cement-based material according to claim 1 is characterized by: The chelating agent is 2 to 5 parts, and the crystal precipitating agent is 2 to 5 parts, wherein the weight ratio of the chelating agent to the crystal precipitating agent is (0.65 to 1.2):
1.
3. The self-repairing crystal anti-seepage high-durability cement-based material according to claim 1 is characterized by: The chelating agent is 3 to 5 parts, and the crystal precipitating agent is 2.5 to 5 parts, wherein the weight ratio of the chelating agent to the crystal precipitating agent is (0.75 to 1.2):
1.
4. The self-repairing crystal anti-seepage high-durability cement-based material according to claim 1 is characterized by: The wear-resistant aggregate is selected from one or more of corundum, high-silicon quartz sand, and ceramic particles.
5. The self-repairing crystal anti-seepage high-durability cement-based material according to claim 1, characterized in that: The water reducing agent is a polycarboxylate water reducing agent.
6. The self-repairing crystal anti-seepage high-durability cement-based material according to claim 1, characterized in that: The retarder is sodium gluconate.
7. The self-repairing crystal anti-seepage high-durability cement-based material according to claim 1 is characterized by: The expansion agent is selected from calcium sulphoaluminate and / or calcium oxide.
8. The self-repairing crystal anti-seepage high-durability cement-based material according to claim 1, characterized in that: The crystal precipitant is selected from one or more of sodium silicate, sodium carbonate and potassium fluoride.
9. Cement-based floor structure, characterized by: The layered structure comprises a concrete base layer, an interface layer and a ground layer in sequence; the raw material of the ground layer is the cement-based material described in any one of claims 1 to 8.
10. A method for paving a cement-based ground structure, characterized in that: include: Applying interface agent on the concrete base to form an interface layer; The cement-based material according to any one of claims 1 to 8 is added with water to form a slurry, and the slurry is spread on the interface layer and cured to form a ground layer; wherein 12 to 16 parts by weight of water are added for every 100 parts by weight of the cement-based material.
Citation Information
Patent Citations
Cement-based permeable crystalline core master batch and its application
CN102875082A
Novel cement-based infiltrating crystalline waterproof material and preparation method therefor
CN105948640A
Manufacturing method of permeable crystallization type waterproof material capable of repairing cracks rapidly
CN108101443A
Permeable crystallization type waterproof paint
CN108996973A
Microcapsule self-healing material which has easy-degradation capsule walls and is applied to fine cracks and micro cracks of concrete
CN110510910A